Sosialisasi Pencegahan Judi Online dan Pinjaman Online Bagi Kalangan Muda di Desa Jimbaran Kulon - Suyono Suyono; Cindi Aprilia; Novy Adryani; Lusiana Zanati; Ahmad Wasi’ Amrullah; Dian Safitri; Shentyia Rindang; Akhmad Barzanji (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This socialization was carried out due to the rise of online gambling and online loans which are currently carried out by many people. Online Gambling and Online Loans have a bad impact on the perpetrators who do it and can harm many people. The many Online Gambling and Online Loan services that can be downloaded through smartphones make it easier for people to carry out this detrimental activity. Therefore, this socialization aims to provide knowledge and provide advice so that young people in Jimbaran Kulon Village can carry out positive activities that can reduce the use of Online Gambling and Online Loans. The research methods used were survey methods, material presentation, and questionnaire distribution distributed to young people in Jimbaran Kulon Village. This socialization was attended by 25 young people with a little discussion about Online Gambling and Online Loans. The socialization carried out can be said to be going well, this can be proven by the response of young people at the time this socialization was carried out.